The Forty-Niners: A Chronicle of the California Trail and El Dorado - White, Stewart Edward, 1873-1946 (Salt Lake City, UT : Project Gutenberg, 2004)
"The Forty-Niners: A Chronicle of the California Trail and El Dorado" by Stewart Edward White is a historical account written in the early 20th century. The book chronicles the transformative period of the California Gold Rush, detailing the diverse groups and individuals involved in the migration westward, and the subsequent changes in California's society and culture during the 1840s and 1850s. The opening of the book sets the stage by examining California's rich historical tapestry, beginning with its Spanish occupation and highlighting the complexities of the period before the American Gold Rush. White describes the transition from the romanticized Spanish days to the more chaotic American presence, outlining the social dynamics and cultural contrasts between the Californians and the incoming settlers. He reflects on the shortcomings of Spanish governance, which failed to develop agriculture and industry, and sets up the narrative that will explore how the discovery of gold would radically alter the landscape and demographics of the region. (This is an automatically generated summary.)
Release date is 2004-06-28
Produced by Suzanne Shell and PG Distributed Proofreaders
Keywords: California -- History; California -- Gold discoveries; California National Historic Trail